A Weighted Scoring Based Rating Scale to Identify the Severity Level of Mathematics Anxiety in Students - Tamal, Maruf Ahmed; Akter, Rabia; Hossain, Syed Akhter; Rezaul, Karim Mohammed (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The purpose of the current study was to develop an effective scale that can be used to assess the severity level of Mathematics Anxiety (MA) among students. Generally, measures for assessing MA adopt primitive questionnaires and unweighted rating-scale based approaches which are predominantly intended for a particular range of students. As a consequence, this type of approach is inherently static and not effective to be used widely. To bridge this gap, considering the view of 839 students, the present study has proposed a Weighted Scoring Based Mathematics Anxiety Rating Scale (WSB-MARS) which represents a more reliable, valid, generalized, and new approach to assess the severity level of mathematics anxiety in students. Besides, the proposed scale can be implemented as a mobile application that is applicable to the research & education field.